Use of a Minimally Invasive Cardiac Output Monitor to Optimise Haemodynamics in a Patient with Mitral Valve Disease Undergoing Cerebrovascular Surgery - Ali M. Al-Mashani; Niranjan D. Waje; Neeraj Salhotra; Samaresh Das; Neelam Suri; Rashid A. Al-Sheheimi; Nilay Chatterjee (Sultan Qaboos University Medical Journal, 2017)
Patients with mitral valve disease undergoing cerebrovascular surgery face increased inherent risks due to their associated cardiac comorbidities. As such, the anaesthetic management of such patients is distinctly challenging. Simultaneous consideration of both the cerebrovascular and underlying cardiac conditions determines key anaesthetic issues, as fluids and vasopressors or inotropes need to be titrated according to haemodynamic variables in order to optimise cerebral blood flow without compromising cardiac function. We report a 45-yearold female patient with mild mitral stenosis and moderate-to-severe mitral regurgitation who presented to the Khoula Hospital, Muscat, Oman, in 2016 following a ruptured anterior communicating artery aneurysm requiring urgent surgical intervention. As highlighted in this case, the VolumeView EV1000™ (Edwards Lifesciences, Irvine, California, USA) system is a minimially invasive haemodynamic monitor that can help immensely in the perioperative management of such patients.